Pengaruh Aplikasi (Napthalene Acetic Acid) dan Lama Perendaman Terhadap Pertumbuhan Awal Bibit Bud Set Tebu (Saccharum Officinarum L.) - Yusi Nur Maskurah; Setiyono Setiyono; Dwi Erwin Kusbianto; Susan Barbara Patricia SM; Hasbi Mubarak Suud (Pro-Life, 2025)
The problem with cultivating the sugarcane bud set technique is how to stimulate the rapid formation of roots and shoots. The effort that can be made is by providing growth regulators. This research aims to determine the interaction between giving NAA concentration (Napthalene Acetic Acid) and soaking time on the initial growth of sugarcane bud set seedlings. This research was conducted using a Completely Randomised Factorial Design with two factors. Factor I is the NAA concentration, which consists of four levels: zero ppm (A1), 50 ppm (A2), 100 ppm (A3), and 150 ppm (A4). Factor II is the length of soaking, which consists of four levels: 0 minutes (S1), 20 minutes (S2), 40 minutes (S3), and 60 minutes (S4). The research results showed that (1) there was an interaction between NAA concentration and soaking time, which had a significant effect on the number of leaves. The best treatment combination is an NAA concentration of 50 ppm (A2) and a soaking time of 20 minutes (S2). (2) The NAA concentration has no significant effect on any of the observed variables. (3) Soaking time has a significant effect on root volume, with the optimal treatment being 20 minutes of soaking time (S2).